2020
DOI: 10.1186/s12960-020-0455-4
|View full text |Cite
|
Sign up to set email alerts
|

A scoping review on family medicine in sub-Saharan Africa: practice, positioning and impact in African health care systems

Abstract: Background: Family medicine (FM) is a relatively new discipline in sub-Saharan Africa (SSA), still struggling to find its place in the African health systems. The aim of this review was to describe the current status of FM in SSA and to map existing evidence of its strengths, weaknesses, effectiveness and impact, and to identify knowledge gaps. Methods: A scoping review was conducted by systematically searching a wide variety of databases to map the existing evidence. Articles exploring FM as a concept/philoso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(61 citation statements)
references
References 67 publications
(96 reference statements)
0
61
0
Order By: Relevance
“…Participants suggested ways that FP training could be expanded to incorporate aspects of the nexus in curricula, for example, the social and environmental determinants of health, or emergency responses to disasters. Authors have identified opportunities for training and research for FPs and primary care providers to strengthen the resilience of communities and to influence policy and research priorities [18,30]. Such public health and emergency medicine functions are still scarce resources in most SSA health districts [19].…”
Section: Interpretation Of the Resultsmentioning
confidence: 99%
“…Participants suggested ways that FP training could be expanded to incorporate aspects of the nexus in curricula, for example, the social and environmental determinants of health, or emergency responses to disasters. Authors have identified opportunities for training and research for FPs and primary care providers to strengthen the resilience of communities and to influence policy and research priorities [18,30]. Such public health and emergency medicine functions are still scarce resources in most SSA health districts [19].…”
Section: Interpretation Of the Resultsmentioning
confidence: 99%
“…Many LMICs are experiencing challenges in implementing a primary health care approach as the role of family medicine, and training strategies and pathways are developed. Challenges include a low profile of family medicine, strengthening governance of primary care, unclear roles and responsibility for family medicine physicians, public mistrust in rural and primary health care providers, provision of appropriate training for the local context, limited infrastructure and supplies, and lack of evidence to inform policy makers (27,28). While learners from LMICs in our study showed a high intent to practice in rural areas, a lack of policy support may pose significant challenges in realizing a rural workforce.…”
Section: Discussionmentioning
confidence: 99%
“…1,2,3,4,5,6 Although the roles of the family physician differ between countries and are still debated, it is clear that in Africa, the family physician often works at the district hospital as well as in primary care teams. 7,8,9 Their roles are often different from that of family physicians in more highly resourced countries and they are seldom the first point of contact, which is usually with a nurse or clinical officer. 10 Primary Care and Family Medicine Education network (Primafamed) is a network of academic departments of family medicine and primary care in sub-Saharan Africa (see: primafamed.sun.ac.za).…”
Section: Introductionmentioning
confidence: 99%